A comparative study of cardiovascular stress during different swimming strokes - Gupta, S.; Goswami, A. (2001)
The study was aimed: (i) to compare maximum heart rate during exhaustive running (HRmasr) and swimming (HRmaxs), (ii) to compare heart rate (HR) in various modes of swimming-front crawl (FC), butterfly (BF), breast stroke (BRS) and back stroke (BS). HRmaxr (192.3 +/- 4.9 beats/min) of the swimmers (N = 7) was higher, although not significantly (P < 0.05), than their HRmaxs (183.7 +/- 3.8). Peak HR of the swimmers in FC, BF, BRS and BS (each of 100 m distance) were 179.9 +/- 7.2, 180.3 +/- 7, 178.6 +/- 6.2 and 177.3 +/- 5.4 beats/min respectively. Average HR in the respective events were 167.3 +/- 15.8, 166.6 +/- 14.1, 163.3 +/- 13.5 and 165.8 +/- 14.6 beats/min. Differences were not significant between any two modes, either in peak HR or mean HR. The results conclude that: (i) maximum HR in swimming is approximately 8 beats/min lower than maximal running and (ii) when the effort is maximum, cardiovascular stress remains unaltered in different swimming modes. Indian J Physiol Pharmacol 2001 Apr;45(2):245-8